Penerapan Model Pembelajaran Two Stay Two Stray Dengan Media KADO (Kartu Budaya Indonesia) untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV - Pruistin, Windi Adhani; Hanifah, Nurdinah; Aeni, Ani Nur (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This research is motivated by the importance of using appropriate learning models and media to improve students' IPS learning outcomes. The low IPS student learning outcomes of 18 students, only 6 students (33%) achieved the KKTP with an average student learning outcome score of 62,4. This research aims to improve IPS learning outcomes through implementing the two stay two stray learning model. This research is classroom action research carried out at SDN Sukadana, Sumedang Regency, with the subjects of this research being fourth grade students. The results of this research show that the two stay two stray learning model has an influence on the learning outcomes of class IV students as evidenced by the increase in learning outcomes in each cycle so that this research has a significant influence on the IPS learning outcomes of class IV students, especially on the material on ethnic and cultural diversity with KADO (Kartu Budaya Indonesia) media. This is proven by: (a) student activity in cycle I obtained 79,3 percent, in cycle II it was 86,3 percent, and in cycle III it was 90 percent; (b) the average student learning outcome in the initial data was 62,4, then in cycle I it was 67,9, then increased in cycle II and cycle III by 76,7 to 86,8 in the complete category. Thus the two stay two stray learning model can be an alternative learning model used in the classroom.